Fodder oat (avena sativa l.) seed production: date of sowing and cutting stubble height effect on seed yield and quality - Digamber; R. C. Poonia; Mor, V S; Nidhi; Kumar, Rahul; Gagandeep Singh (Journal of Cereal Research, 2024)
The investigation was carried out to study the effect of date of sowing and cutting stubble height on Seed Yield and Quality. It is concluded that to produce quality seed of oat, the crop should be sown in early November. The maximum seed yield and better seed quality were found in normal date sown crop D1 (6th November), whereas low seed yield and poor seed quality was found in very late sowing D3 (2nd January). The cutting stubble heights have significantly affected the seed yield and quality of oat in case of dual (fodder + seed) crop of oat. The crop without cutting produced the highest yield and better quality seed. But for getting additional fodder yield alongwith better quality seed, foliage cut should be taken at stubble height of 10-15cm. stubble height lesser than 10cm increase the fodder yield a little but reduce the seed yield and quality significantly.